E-learning for Prisoners. Experience from Sweden, Norway, Poland, Finland and Germany - Becker-Pestka, Daria Joanna (International Journal of Research in E-learning, 2022)
In the following article a discussion on the use of e-learning in education of convicts is presented. The topic discussed by the Author is connected with the fact that the use of new media in education at present has become a common solution applied also to educate inmates. E-learning is a current form of education and vocational training. It provides improvement of contemporary culture in education applied at penitentiary institutions to educate convicts. E-learning helps and lets prisoners obtain education and to update education differences. As a method of education, it requires users’ autonomy and self-discipline while working with the use of digital platforms. Education must respond to different needs expressed by the evolving knowledge society. It mainly concerns education of people at risk of social exclusion, e.g. convicts. It is related to the need of dealing with and solving problems that pertain to such issues as increasing possibilities of the media in the area of generating, processing and creating information. The aim of the article is also to describe the use of e-learning in European countries such as Sweden, Norway, Poland, Finland and Germany. These countries were selected for the analysis because they appreciate modern technologies in penitentiary work. They change and develop the solutions. The experience in the use of e-learning in penitentiary work with inmates in Sweden, Norway, Poland, Finland and Germany is different. The aim of the article is also to show how modern technology can be applied in working with convicts. E-learning becomes a tool used for preventing exclusion. Development of various technologies makes it possible to support convicts and prison staff members in the process involving correctional activities. Technologies offer a chance to return or to start work, to continue education, to meet the needs of one’s family, to have an active life in accordance with the social principles after leaving prison. E-learning provides people who have been isolated in prison with a real chance to acquire qualifications. Hence, social issues, family interests, individual interests, business and modern technological solutions are combined in the same field. Coherent and efficient activities come as a challenge to those who perform them and to the society; however, these activities support the process of social rehabilitation.